2010
DOI: 10.1177/030857591003400403
|View full text |Cite
|
Sign up to set email alerts
|

Paired Reading as a Literacy Intervention for Foster Children

Abstract: The education of children in foster care has long been considered problematic. One contributing factor may be the lack of educational support from key adults in these children's lives. High turnover of school and home placements may preclude the presence of a consistent adult who is actively involved in a foster child's education. Moreover, research suggests that education is sometimes viewed as a low priority by carers in comparison with other aspects of a foster child's life. The aim of the study reported he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 12 publications
(21 reference statements)
2
24
0
1
Order By: Relevance
“…Adding the presumed time effect (0.33 years ¼ 4 months) we get figures that correspond to total gains in reading age during the trial: 11.3 and 11.0 months. This is very similar to the result found in the UK Paired Reading trial (Osborne, Alfano and Winn, 2010;. The effect sizes were 0.38 and 0.27, well above the limit for 'substantial improvement' according to the US What Works Clearinghouse (2008) recommendations.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Adding the presumed time effect (0.33 years ¼ 4 months) we get figures that correspond to total gains in reading age during the trial: 11.3 and 11.0 months. This is very similar to the result found in the UK Paired Reading trial (Osborne, Alfano and Winn, 2010;. The effect sizes were 0.38 and 0.27, well above the limit for 'substantial improvement' according to the US What Works Clearinghouse (2008) recommendations.…”
Section: Resultssupporting
confidence: 86%
“…We replicated a UK literacy intervention (Osborne, Alfano and Winn, 2010; targeting children in foster care age 8-12, with a larger sample (n ¼ 81) and a wider range of follow-up data compared to the UK study. These data included information collected each week on programme compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that paired reading improves the literacy skills of children in foster care and that this strategy renders the act of reading highly enjoyable for boys and girls (Forsman, 2015;Osborne, Alfano, & Winn, 2013). Paired reading has historically been defined as a procedure to accelerate reading based on different stages.…”
Section: Dialogic Literary Gatherings (Dlgs) In the Social Exclusiomentioning
confidence: 99%
“…Previous studies indicate that paired reading offers a constructive way of improving looked-after children's literacy skills (Osborne et al 2010;Vinnerljung et al 2014). However, these studies provide little insight into the process of the intervention, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, some promising interventions exist (Forsman & Vinnerljung 2012;Liabo et al 2013). Studies have reported successful outcomes when involving foster carers in a paired reading intervention, both in a British (Osborne et al 2010) and a Swedish trial .…”
Section: Introductionmentioning
confidence: 99%